Effects of minocycline on cocaine sensitization and phosphorylation of GluR1 receptors in 5-lipoxygenase deficient mice - Chen, Hu; Manev, Hari (Neuropharmacology, 2011)
In wild-type (WT) mice, the antibiotic minocycline inhibits development of cocaine-induced locomotor sensitization. Some of the actions of minocycline may involve the 5-lipoxygenase (5-LOX) pathway. We used the model of 5-LOX-deficient mice to investigate whether 5-LOX participates in minocycline’s influence on the effects of cocaine. Locomotor sensitization was induced by 4 daily cocaine injections and the phosphorylation status of GluR1 glutamate receptors was assayed in brain samples. Minocycline failed to affect cocaine sensitization in 5-LOX-deficient mice. In these mice, neither cocaine nor minocycline 4-day treatment altered GluR1 phosphorylation. In WT mice in which minocycline inhibited development of cocaine sensitization, a 4-day cocaine treatment increased GluR1 phosphorylation at both Ser831 and Ser845 sites in the frontal cortex but not the striatum; further, this effect was prevented by minocycline. Under basal conditions and in response to a single cocaine injection the levels of GluR1, GluR2, and GluR3 AMPA receptor subunits did not differ between WT and 5-LOX-deficient mice, but the response of GluR1 phosphorylation to a single cocaine injection was greater under the 5-LOX deficiency. Hence, in WT mice GluR1 phosphorylation increased only in the frontal cortex and only at the Ser831 site. In 5-LOX-deficient mice, acute cocaine injection increased both Ser831 and Ser845 phosphorylation both in the frontal cortex and in the striatum. We suggest that in studying minocycline’s action on cocaine’s effects and/or addiction in humans, it would be important to consider the characterization of the subjects’ 5-LOX system. This article is part of a Special Issue entitled ‘Trends in Neuropharmacology: In Memory of Erminio Costa’.